A sign of acute inflammation in type 2 diabetes mellitus patients in Kota Baru and Kalibaru subdistricts, Bekasi - Ria Amelia; Neni Arshita; Siti Nur Fajriah; Chandra Vina Dwi Astuti; Islamiyah Nurul Fitri (Acta Biochimica Indonesiana, 2019)
Background: During the development of chronic type 2 diabetes mellitus (T2DM), inflammatory signals are elevated which can cause microvascular damage. C-Reactive Protein (CRP) is one of acute phase proteins stimulated under inflammatory conditions and creatinine is a waste product used to measure the glomerular filtration rate (GFR). Both of these compounds are considered as biomarkers of acute kidney damage among people with T2DM. Objective: The purpose of this study was to determine relationship between CRP and creatinine levels in T2DM patients. Methods: We conducted analytic cross-sectional study in Kota Baru and Kalibaru sub-districts, Bekasi, from January until February 2019. Creatinine was measured using the jaffe method and CRP was measured using a latex agglutination technique. The correlation between CRP and creatinine was analyzed with Spearman test. Results: Spearman correlation test from 55 samples showed a weak positive correlation (r = 0.289 ; p < 0.05) between CRP levels and creatinine levels. These results indicate that high CRP levels are directly proportional to creatinine levels in the serum of T2DM patients. Creatinine and CRP levels can be used as clinical parameters as biomarker for acute microvascular damage in nephron cells that can develop into complications due to T2DM. Conclusion: There was a significant, weak positive correlation between CRP levels and creatinine levels in T2DM patients in Kota Baru and Kalibaru districts, Bekasi